2006
DOI: 10.1074/jbc.m605458200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of ASC2, a Pyrin Domain-only Protein That Regulates Inflammatory Signaling

Abstract: Pyrin domain (PYD)-containing proteins are key components of pathways that regulate inflammation, apoptosis, and cytokine processing. Their importance is further evidenced by the consequences of mutations in these proteins that give rise to autoimmune and hyperinflammatory syndromes. PYDs, like other members of the death domain (DD) superfamily, are postulated to mediate homotypic interactions that assemble and regulate the activity of signaling complexes. However, PYDs are presently the least well characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 65 publications
2
55
0
Order By: Relevance
“…5B). These data are consistent with a conserved binding mode of the ASC PYD with these (42), and NLRP3 (Protein Data Bank ID code 3QF2) (39) were aligned using PyMOL, and the residues important for interaction of the ASC PYD are indicated with acidic residues in red and basic residues in blue. C, surface electrostatic potential of the PYDs of ASC, POP1, and NLRP3 shown in the same orientation as B.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…5B). These data are consistent with a conserved binding mode of the ASC PYD with these (42), and NLRP3 (Protein Data Bank ID code 3QF2) (39) were aligned using PyMOL, and the residues important for interaction of the ASC PYD are indicated with acidic residues in red and basic residues in blue. C, surface electrostatic potential of the PYDs of ASC, POP1, and NLRP3 shown in the same orientation as B.…”
Section: Resultsmentioning
confidence: 53%
“…Because NLRP3 assembles into an oligomer (6), its interaction with ASC PYD is likely to be promoted by self-association because of increased contacts between self-associated ASC and the NLRP3 oligomer as in our model. However, because POP1 is a monomer (42), ASC selfassociation does not promote its interaction. The fact that overlapping sites on ASC PYD interact with POP1 and NLRP3 suggested that POP1 may inhibit interaction of ASC with NLRP3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding how NLRP7 mediates signal transduction at a molecular level may provide new therapeutic approaches to these diseases. Despite the abundance of PYDs in several protein families, structural information about PYDs is very limited (31)(32)(33)(34). Currently, only a few structures of effector domains involved in NLR signaling are known.…”
mentioning
confidence: 99%